Citrus is a Multivitamin Treasure Trove: A Review - Budiarto, Rahmat; Mubarok, Syariful; Nursuhud, Nursuhud; Rahmat, Bayu Pradana Nur (Department of Agronomy and Horticulture, IPB University, 2023)
Citrus is popularly known as the source of beneficial and essential nutrients for human health, including vitamins. The current review revealed the content of multivitamins, not only vitamin C but also vitamins A, B, and E that are not widely acknowledged within Citrus. Numerous Citrus genotypes contain vitamin C, with the grapefruit (Citrus paradisi) being the richest, and citron (C. medica) the poorest. Vitamin A in the form of β-carotene, α-carotene, and β-cryptoxanthin is commonly found within Citrus, especially in several colored flesh species such as grapefruit, mandarin (C. reticulate), and orange (C. sinensis). In terms of vitamin B, orange and grapefruit are proven to contain B-complex, including thiamine (B1), riboflavin (B2), niacin (B3), pantothenic acid (B5), pyridoxine (B6), biotin (B7), inositol (B8) and folate (B9). Vitamin E in the form of α-tocopherol was detected in leaf kaffir lime (C. hystrix) and orange (C. sinensis), lemon (C. limon), mandarin (C. reticulate), and tangerine (C. nobilis) fruit. This review summarizes the nutritional content of Citrus; Citrus contains not only vitamin C but also other vitamins beneficial to human health, therefore Citrus consumption is highly recommended.